Fractalkine Receptor CX3CR1 Is Expressed in Epithelial Ovarian Carcinoma Cells and Required for Motility and Adhesion to Peritoneal Mesothelial Cells - Kim, Mijung (2011)
Epithelial ovarian carcinoma is a deadly disease, and little is known about the mechanisms underlying its metastatic progression. Using human specimens and established cell lines, we determined that the G protein-coupled seven-transmembrane fractalkine receptor (CX(3)CR1) is expressed in primary and metastatic ovarian carcinoma cells. Ovarian carcinoma cells robustly migrated toward CX(3)CL1, a specific ligand of CX(3)CR1, in a CX(3)CR1-dependent manner. Silencing of CX(3)CR1 reduced migration toward human ovarian carcinoma ascites fluid by approximately 70%. Importantly, adhesion of ovarian carcinoma cells to human peritoneal mesothelial cells was dependent on CX(3)CL1/CX(3)CR1 signaling. In addition, CX(3)CL1 was able to induce cellular proliferation. Together, our data suggest that the fractalkine network may function as a major contributor to the progression of epithelial ovarian carcinoma, and further attention to its role in the metastasis of this deadly malignancy is warranted.